Optimasi Formula Krim Ekstrak Etanol Daun Kelor (Moringa oleifera Lamk) Dengan Emulgator Span 80 Dan Tween 80 - Diyah Ayu Wulandari; Putra Mahardika, Muladi; Siska Wardani, Tatina (Media Farmasi Indonesia, 2022)
Moringa plant (Moringa Oleifera Lamk) contains various free radical inhibitory molecules, such as phenolic compounds (phenolic acids, flavonoids, quinones, coumarins, lignans, stilbenes, tannins), nitrogen compounds (alkaloids, amines, betalains), vitamins, terpenoids (including carotenoids). ), and several other endogenous metabolites rich in antioxidant activity. When span 80 and tween 80 are mixed in a suitable composition and in their manufacture the aqueous phase is dispersed into the oil, span 80 and tween 80 will be arranged alternately at the interface of the oil phase and water phase forming a monolayer that surrounds the droplets so as to produce good emulsifying properties. and form a stable O/A type emulsion. In this study, concentration variations were carried out to see the optimum formula for the ethanol extract of Moringa leaf cream with a mixture of span 80 and tween 80 to see the best physical properties. The cream was made in 5 formulas with variations of span 80 and tween 80 using the Simplex Lattice Design method with the parameters of adhesion, dispersion, pH, viscosity, and protective power. Data that were normally distributed were followed by One Sample T-test, one sample with 95% confidence level. The optimum formula is found in a concentration ratio of span 80: tween 80 (0:1) with a desirability value obtained that is 0.986.